Psychosocial adjustment in infertility: a comparison study of infertile couples, couples undergoing assisted reproductive technologies and presumed fertile couples - Moura-Ramos, Mariana (2010)
The aim of the present study was to investigate psychosocial adjustment and infertility related stress of infertile couples and couples undergoing Assisted Reproductive Technologies (ART). In a cross sectional study, 148 couples were recruited: 79 couples undergoing ART, 25 infertile couples in their first medical appointment in an infertility centre and no previous ART treatments and 44 childless couples in reproductive age without infertility history. Measures assessed emotional adjustment, quality of life, marital relationship and infertility stress. Couples were the focus of the analysis. Results indicated that couples undergoing ART presented more adjustment difficulties, especially women. No significant differences were found in marital adjustment, although ART couples idealized their marital relationship to a higher degree. Results are discussed in terms of clinical implications and future research directions.